The Arms and the heroes putted on to play: The Lusiads transposition to a boardgame - Thimóteo, Saulo Gomes (Revista Desassossego, 2023)
The Luís de Camões’ epic work has been adapted to multiple supports (visual arts, films, graphic novels), something that expands The Lusiads universe sight and establishes itself as a book’s revisitation toward new interpretations. This article proposes a boardgame as a reading strategy and an interaction with the episodes and storylines under a gameplay perspective, regarding to a spread of Camões’ verses, relying on the work’s symbols and impressions readings, as well as adaptation and playfulness theories.